Avaliação morfológica e imuno-histoquímica de carcinomas de células escamosas cutâneos em cães e gatos - Santos, Alex dos (2022)
This doctoral thesis was divided into three parts, resulting in three scientific articles. The first article aimed to investigate the presence of lesions indicative of solar or viral etiology in cutaneous squamous cell carcinomas (SCCs) of dogs and cats and to relate them to the expression of p53 and p16 proteins, and to evaluate the degree of intraepidermal pigmentation. A total of 152 cases of SCCs were evaluated, 89 in dogs and 63 in cats. Lesions indicative of solar etiology (55/152) predominated in SCCs in region exposed to solar radiation. There was a statistically significant association between histological lesions indicative of solar etiology with a low degree of intraepidermal pigmentation in SCCs of dogs and cats. A statistically significant association between histological lesions indicative of solar etiology and p53 expression was observed only in dogs. On the other hand, lesions suggestive of a viral etiology (19/152) were frequent in SCCs in regions protected from solar radiation. There was a statistically significant association between lesions suggestive of viral etiology and p16 expression only in SCCs in cats. Immunostaining for papillomavirus was rarely present (in p16 positive cases and with lesions suggestive of viral origin). The second study aimed to evaluate the prevalence and anatomopathological characterization of metastatic SCCs in dogs and cats. In 36 years, 478 cases of SCCs were received for diagnosis, among which metastases were present in 21 cases (4.39%), twelve in dogs (57%) and nine in cats (43%). Regional metastases predominated. Lymph nodes (19/21) and lung (7/21) were the most affected organs. Moderately differentiated SCCs metastasized more frequently (9/21). The mitotic count and the AgNOR index varied greatly between species and between histological grades. The collective migration and invasion pattern predominated in the well-differentiated SCCs and the individual cell pattern in the poorly-differentiated SCCs. All metastatic SCCs were associated with a marked desmoplastic reaction. The presence of myofibroblasts was detected by immunohistochemistry (IHC) in the desmoplastic reaction, mainly in the “tumor invasion front”. The third article aimed to report two unusual cases of SCCs with mucinous metaplasia in dogs. On histology, both dogs showed a proliferation of neoplastic keratinocytes with intratumoral mucin production. From the histological findings associated with an IHC panel, it was possible to rule out other differential diagnoses. Thus, this report described the mucin-producing subtype in two cutaneous SCCs in dogs.